2018
DOI: 10.1002/zoo.21463
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary observations of an unusual mouth interaction between beluga calves (Delphinapterus leucas)

Abstract: Although many animals, including odontocetes, exhibit interactions involving mouths (e.g., mouthing, nuzzling, biting), a limited number of animals display mouth‐to‐mouth social interactions that involve mutual coordination and collaboration. The purpose of this paper is to describe briefly a spontaneous and unexpected mouth‐to‐mouth social interaction between beluga calves in human care during their first year of life. Forty‐seven independent events were identified after event sampling from more than 345 hr o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The behavior and social interactions of a relatively stable white whale, or beluga ( Delphinapterus leucas ) population at a North American facility has been studied systematically since 2007. From long-term weekly documentation calf behavioral development and maternal care, behavioral milestones, such as nursing, swim positions, locomotor development, social interactions, and play behaviors have been established and validated with belugas from other facilities and in their natural habitat (Krasnova et al, 2006, 2009; Hill, 2009; Karenina et al, 2010, 2013; Hill et al, 2013, 2018a; Hill and Campbell, 2014; Hill and Ramirez, 2014). Maternal care behaviors are conserved across both habitats (Krasnova et al, 2006, 2009; Hill, 2009; Karenina et al, 2010, 2013; Hill et al, 2013, 2017), but show individual variation much like bottlenose dolphins in human care or the wild (Hill et al, 2007; Gibson and Mann, 2008; Stanton and Mann, 2012).…”
mentioning
confidence: 99%
“…The behavior and social interactions of a relatively stable white whale, or beluga ( Delphinapterus leucas ) population at a North American facility has been studied systematically since 2007. From long-term weekly documentation calf behavioral development and maternal care, behavioral milestones, such as nursing, swim positions, locomotor development, social interactions, and play behaviors have been established and validated with belugas from other facilities and in their natural habitat (Krasnova et al, 2006, 2009; Hill, 2009; Karenina et al, 2010, 2013; Hill et al, 2013, 2018a; Hill and Campbell, 2014; Hill and Ramirez, 2014). Maternal care behaviors are conserved across both habitats (Krasnova et al, 2006, 2009; Hill, 2009; Karenina et al, 2010, 2013; Hill et al, 2013, 2017), but show individual variation much like bottlenose dolphins in human care or the wild (Hill et al, 2007; Gibson and Mann, 2008; Stanton and Mann, 2012).…”
mentioning
confidence: 99%
“…More detailed studies in captivity have expanded upon those observations and add to the growing evidence for certain types of social play, such as mouth-to-mouth social play (Hill, Dietrich et al 2019). Hill & Ramirez (2014) demonstrated that in addition to calves and juveniles, adult belugas also engaged in play behaviours; males engaged in more play bouts and a higher percentage of locomotor play activities.…”
Section: Play Behaviourmentioning
confidence: 99%
“…MtMIs were identified according to the T A B L E 1 Demographics on juvenile belugas followed in this study. description provided by Hill et al (2019). All the MtMIs were considered to be a type of play fighting, rather than aggression, as they satisfied Smith's (1997) criteria for distinguishing play fighting from serious fighting.…”
Section: Video Analysismentioning
confidence: 99%
“…social preference in sexual play is true of other forms of social play in belugas, a detailed investigation of MtMIs was conducted. As an exploratory descriptive study of mouth-to-mouth play behaviors in a group of belugas observed over a 12-year study period, this study expanded on the initial report by Hill et al (2019). We explored the frequency of behaviors, age and sex biases, partner preferences, seasonality and correlation with social behavior, and the developmental time course to better understand the possible functions of MtMIs.…”
mentioning
confidence: 99%